Impact of Political Conflict on Democratic Reform: A Global Perspective - Thapa, Santa Bahadur (NUTA Journal, 2024)
The Complex and Multifaceted Interaction between Political Conflict and democratic reform As part of their argument, this paper analyses the inter-relationship between political divisions and democracy, discussing how political conflict can potentially be both a driver of democratic progress and a risky destabilizer. It explores forms of political conflict and their origins, from peaceful protests to violent uprisings, and their sources, whether socio-economic grievances, identity-based divisions, ideology-based divergences, or institutional weakness. It elucidates how conflict can spur political participation, reveal institutional failings, encourage dialogue and compromise, and increase accountability, all of which will push democratic reform. However, the piece admits it can also have downsides, from political polarization, at least in the short run, to gridlock and the erosion of trust in democratic institutions. The assessment emphasizes that conflict needs to be managed constructively through sound institutions, inclusive dialogue, and addressing deep-seated grievances in the long run. It reflects the need for a finer-grained understanding of political conflict dynamics, emphasizing the importance of each person's role in navigating democratic reform in an increasingly interdependent and polarized world.